2012
DOI: 10.5120/5503-7503
|View full text |Cite
|
Sign up to set email alerts
|

SVM and Neural Network based Diagnosis of Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is an eye disease caused by the complication of diabetes and we should detect it early for effective treatment. As diabetes progresses, the vision of a patient may start deteriorate and lead to diabetic retinopathy. As a result, two groups were identified, namely nonproliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR). In this paper, to diagnose diabetic retinopathy, two models like Probabilistic Neural network (PNN) and Support vector machine (SVM) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 19 publications
(13 reference statements)
1
24
0
Order By: Relevance
“…In a study to compare NN and SVM for diagnosing diabetic retinopathy, Priya and Aruna [15] reported better performance for SVM (accuracy 89.6% for NN and 97.61% for SVM). In a study comparing three data mining methods (NN, SVM, and decision tree) with LR, Kim et al [10] concluded that the decision tree algorithm slightly outperformed (AUC, 0.892) the other data mining techniques, followed by the artificial neural network (AUC, 0.874) and SVM (AUC, 0.876), which is in contradiction to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study to compare NN and SVM for diagnosing diabetic retinopathy, Priya and Aruna [15] reported better performance for SVM (accuracy 89.6% for NN and 97.61% for SVM). In a study comparing three data mining methods (NN, SVM, and decision tree) with LR, Kim et al [10] concluded that the decision tree algorithm slightly outperformed (AUC, 0.892) the other data mining techniques, followed by the artificial neural network (AUC, 0.874) and SVM (AUC, 0.876), which is in contradiction to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [9] compared SVM and LR for the classification of undiagnosed diabetes or pre-diabetes vs. no diabetes. Priya and Aruna [15] compared NN and SVM for the diagnosis of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are some developments on automatic systems that provide a more detailed classification of diabetic retinopathy stages namely, normal, nonproliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) [31][32][33]56]. Some developed systems focus on the detection of diabetic retinopathy features, such as microaneurysms, exudates, hemorrhages and others.…”
Section: Microaneurysm Detection Methodsmentioning
confidence: 99%
“…The proposed system uses colour fundus images, where the features are extracted from the raw image by using various image processing techniques and fed into a Support Vector Machine (SVM) for classification. The system has been later enhanced by combining two types of classifiers, a Probabilistic Neural Network (PNN) and a Support Vector Machine [32].…”
Section: Previous Related Workmentioning
confidence: 99%
“…Quellec et al [16] generated an optimal set of filters to distinguish the lesions. Priya et al [17] proposed a method to diagnose DR, and the performances of SVM and PNN were analysed. The region of interest (ROI) was segmented using the FCM means algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%